WHAT IT MEANS TO BE A MAN: RETHINKING MASCULINITY IN POPULAR CHICK LIT THE BOY NEXT DOOR BY MEGGIN CABOT - Agnesthy LH Gratia, - (2012)
The study is entitled What It Means To Be A Man: Rethinking Masculinity In Popular Chick Lit "The Boy Next Door" by Meggin Cabot. It is aimed at investigating the construction of male characters in the novel and the ways it is viewed through the perspectives of masculinity. The data are collected from the novel of The Boy Next Door in a form of textual evidence that related to the characterizations of the male characters. The study employs descriptive qualitative approach and textual analysis method to make a systematic description of the collected data. To analyze the data, theory related to masculinity by Beynon (2007), Connell (2003) and Cohen and Wilber (2009) are employed. The findings show that male characters are constructed through four categories i.e. looks, popularity, masculinity and romantic tendency. Ii is also found that the masculinity of the male characters is divided into two types, the hegemonic masculinity and feminized masculinity. Therefore, it is concluded that the two concepts of masculinity are influenced by cultural factors.